Efficacy evaluation of the school program Unplugged for drug use prevention among Brazilian adolescents. (December 2016) - Sanchez, Zila; Sanudo, Adriana; Andreoni, Solange; Schneider, Daniela; Pereira, Ana; Faggiano, Fabrizio
Abstract Background Most Brazilian schools do not have a continuous program for drug use prevention and do not conduct culturally adapted activities for that purpose. This study evaluated the impact of theUnplugged program on drug use prevention among children and adolescents in public middle schools of Brazil. Methods A non-randomized controlled trial was conducted in 2013 with 2185 students in 16 public schools from 3 Brazilian cities. The intervention group attended 12 weekly classes of theUnplugged program for drug use prevention, and the control group did not attend to any school prevention programs in the same year. Multilevel analyses were used to evaluate temporal and between group changes in the consumption of each drug. Results The study suggested that there was no evidence thatUnplugged effected 11- to 12-year-old students. However, the program seemed to stimulate a decrease in recent marijuana use (transition from use to non-use in 85.7% of intervention cases and 28.6% of control cases, OR = 17.5, p = 0.039) among 13- to 15-year-old students. In addition, students in this age range who received theUnplugged program had similar drug consumption levels to those observed before the program began. However, students in the control group presented a significant tendency to increase marijuana use and binge drinking. Conclusions This study adds to the evidence of program efficacy among Brazilian middle school students by presenting marginal effects on binge drinking and marijuana use. An 18-month randomized controlled trial is recommended for a future study.